Design Archade Animated Game War Based on Flash Jedi - Fathiah, Fathiah; Saputra, Hendra (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2016)
War games are already familiar to children today, but with the development of today's computer is one device that can provide many benefits to children in increasing dexterity and brain. War game system that has been often done by children at this time it would be nice to be converted into a game system in the form of computer applications in the form of 2-dimensional game that is easy to play. So oelh because it required a game application design that can run on computers that have a small memory and simultaneously increase the agility and brain of children by building Game Animation 2D-based Arcade Adobe Flash. The purpose of this research is to develop Arcade game application that is educational game that prioritizes on the speed of hand skill in collecting value and winning game by using mouse media. Research produces a computer game that supports 2 dimensional graphics and can run on a CPU that has a small memory has been successfully built and game applications that have been built prioritize on the skills of hand speed using mouse media.Keywords: game Arcade, Adobe Flash, 2 Dimensions